Keseimbangan Aspek Ekonomi, Sosial, dan Lingkungan dalam Tata Kelola Pariwisata Desa: Penerapan Kerangka Triple Bottom Line pada Destinasi Pasar Blumbang Mataram Wirokerten - Muhammad Syahid; Sakir Ridho Wijaya (Universitas Muhammadiyah Ponorogo, 2026)
Village tourism plays an essential role in improving community welfare, yet it often emphasizes economic outcomes over social and environmental aspects. This study examines the implementation of the Triple Bottom Line (TBL) concept at Blumbang Mataram Market, Wirokerten, as a model for sustainable village tourism governance. Using a descriptive qualitative method, data were obtained through in-depth interviews, direct observation, and supporting documentation. Findings indicate that the economic dimension shows the strongest progress, with the number of MSMEs growing from I5 to 75 and average turnover rising by about 35 percent. Socially, the market fosters interaction and cooperation among residents but also inggers jealousy among vendors. Environmentally, a plastic-free policy and natural packaging have been introduced, though waste disposal remains limited to open burning. Overall, TBL implementation is still unbalanced, highlighting the need for policy innovation and multi-sector collaboration to ensure holistic and sustainable tourism development. keyword: Triple Bottom Line; Tourism Village; Sustainability; Blumbang Mataram Market; MSMes;